2005
DOI: 10.1073/pnas.0409792102
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing functional hippocampal pathways in a brain-based device as it solves a spatial memory task

Abstract: Analyzing neural dynamics underlying complex behavior is a major challenge in systems neurobiology. To meet this challenge through computational neuroscience, we have constructed a brain-based device (Darwin X) that interacts with a real environment, and whose behavior is guided by a simulated nervous system incorporating detailed aspects of the anatomy and physiology of the hippocampus and its surrounding regions. Darwin X integrates cues from its environment to solve a spatial memory task. Placespecific unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 40 publications
(37 reference statements)
0
46
0
Order By: Relevance
“…Much attention has also been devoted to emulating navigation and orientation behavior. Examples abound and include visual homing inspired by how bees or wasps find their way back to their nests (12), cricket phonotaxis [how female crickets move toward the mating sounds of males in highly rugged and noisy environments (32)], and spatial memory formation by modeling place fields and head-direction cells which account for the sophisticated navigational skills of rodents (33). One of the important design principles implicitly exploited in the examples above is sensory-motor coordination (34); that is, the mutual coupling of sensing and acting.…”
Section: Embedded Neural Modelsmentioning
confidence: 99%
“…Much attention has also been devoted to emulating navigation and orientation behavior. Examples abound and include visual homing inspired by how bees or wasps find their way back to their nests (12), cricket phonotaxis [how female crickets move toward the mating sounds of males in highly rugged and noisy environments (32)], and spatial memory formation by modeling place fields and head-direction cells which account for the sophisticated navigational skills of rodents (33). One of the important design principles implicitly exploited in the examples above is sensory-motor coordination (34); that is, the mutual coupling of sensing and acting.…”
Section: Embedded Neural Modelsmentioning
confidence: 99%
“…We previously developed a method, called a backtrace procedure (7), that identifies functional pathways by choosing a particular reference neuronal unit at a specific time and recursively examining the previous activities of all neuronal units that caused the observed activity in that reference unit.…”
Section: Neuronal Responses and Synaptic Plasticity Duringmentioning
confidence: 99%
“…To provide a stringent test of this rule, we embodied a cerebellar model incorporating the rule in a brain-based device (BBD) (5)(6)(7)(8), which had to smoothly traverse a curved course outlined by a series of traffic cones. As in other neurorobotic systems (9)(10)(11)(12)(13), the behavior of such a BBD is guided by a simulated nervous system, incorporating features of vertebrate neuroanatomy and neurophysiology, which determine the device's interaction with the environment.…”
mentioning
confidence: 99%
“…During maze navigation, journey-dependent responses emerged in Darwin XI's hippocampal neuronal units. Because the computational design of a BBD allows us to determine the detailed microcircuitry and synaptic activity of all neuronal units, we are able to trace structural and functional connections in complete detail by a procedure called backtrace analysis (16). In the present study, such an analysis of neural population activity revealed the differential contributions of the BBD's cortical sensory areas and hippocampus to the firing of journey-independent and -dependent neuronal units.…”
mentioning
confidence: 79%